Solvable subgroups of maximal order of some finite simple groups of Lie type - Abduh, Abdullah A.; Aldosray, Falih. A.M (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The aim of this work is using the information in the ATLAS of Finite Groups and the GAP computational system , to determine the solvable subgroups of maximal orders in some finite non-abelian simple group of Lie type which have been appeared in the ATLAS. The (p,q,r)-generators , the structures and permutation representations of these subgroups have been found.